Get up, stand up - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Catherine Gatundu describing how the Forest Action Network is helping communities in Kenya to stand up for their rights to clean, safe water.